Factores asociados a la falla de la extubación en recién nacidos pretérminos atendidos en el servicio de neonatología del Hospital Iquitos, 2019-2021 - Sinti Chávez, Roger Francisco Javier (2023)
Failure of extubation in preterm infants is common and reintubation represents an increased risk of complications, so it is essential to identify factors associated with extubation success or failure. For this reason, the present work aims to determine the factors associated with extubation failure in preterm newborns treated in the neonatology service of Hospital Iquitos, 2019-2021. For this, an observational-analytical study was developed, having as a sample 19 intubated preterm newborns, from 28 to 36 weeks of gestational age. Concluding that the prevalence of extubation failure was 15.8%, regarding the clinical-epidemiological characteristics, gestational age presented a statistically significant association with extubation failure (28.3 weeks vs 31.8 weeks, p=0.016), other variables such as weight, Gender, type of delivery, antenatal corticosteroids, gestational hypertension, gestational diabetes, urinary tract infection in the mother, and premature rupture of the membrane were not associated with extubation failure (p>0.05). Regarding hemoglobin, in this study it was observed that there is no statistically significant association between hemoglobin less than 14 g/dL and extubation failure in preterm newborns (p=0.740).